Student Wellbeing Ditinjau dari Keberfungsian Keluarga dan Iklim Sekolah pada Siswa SMK di Kota Makassar - Alexander Indrakusuma Linggi; Ria Sakinah Waji (Journal on Education, 2024)
Abstract Student wellbeing is a condition of positive emotional life in students in the school environment. Wellbeing plays a very important role in the adolescent development process and supports the achievement of learning success at school. The purpose of this study is to determine the relationship between the external system of vocational students (family and school) and their level of well-being. This research method is a correlational study of three research variables namely student wellbeing, family functioning and school climate. The subjects in this study were 140 students from two public vocational schools in Makassar City. The first and second hypothesis tests show that there is a positive and highly significant relationship between family functioning and student wellbeing (r = 0.420; p < 0.01) and there is also a positive and highly significant relationship between school climate and student wellbeing (r = 0.470; p < 0.01). The third hypothesis test uses multiple regression and shows that the variables of family functioning and school climate together are significantly related to student wellbeing of vocational high school students in Makassar City (F = 27.018; df = 2.0; p < 0.01).